Column Strengthening with TRC: Influences of the Column Geometry onto the Confinement Effect - Regine Ortlepp; Andy Lorenz; Manfred Curbach (Advances in Materials Science and Engineering)
The increase of the load-carrying capacity of columns being reinforced with Textile Reinforced Concrete (TRC) is partly achieved by the additional concrete cover. But then it is also decisively caused by the confinement effect of the textile reinforcement. The confinement is thereby producing a three-axial state of stress within the concrete core of the column. The effectiveness of such a confinement is especially dependent on the geometry of the concrete column to be strengthened. At rectangular ones with sharp edges without ogees the TRC strengthening can only augment the load-carrying concrete share not create a confinement effect which can be achieved at the round counterparts. Within the study we tested columns with all possible cross-sections from square to circle with different transition radiuses. Thus the influence of the transition radius onto the local-bearing capacity of the reinforcing textile was recorded. Furthermore the impact of different fibre materials and reinforcement degrees of the TRC-strengthening layer has been examined. The first results show a considerable disproportionate increase of the confinement effect with rising transition radius, as well as a growth of the confinement effect with augmenting level of reinforcement in the TRC-strengthening layer.